Bulk and monolayer thermoelectric and optical properties of anisotropic NbS2Cl2. (March 2023) - Natarajan, Arul Raj; Gupta, Mayanak K.; Mittal, Ranjan; Kanchana, V.
Abstract: Recently, the chalcogenide-based materials are attracting the scientific community due to their promising thermoelectric properties. Monoclinic compounds of the chalcogenide class of materials are the least explored for thermoelectric and optoelectronic device applications. In our present study, we have taken NbS 2 Cl 2 to analyse its electronic properties of bulk and monolayer to understand its electronic and thermal transport properties along with its optical properties, using the density functional theory framework. The investigated compound has direct bandgap values of 1.41 eV and 1.67 eV in its bulk and monolayer phases, respectively, making it a semiconductor. The lattice thermal conductivity( κ l ), being a crucial parameter for a thermoelectric material, is observed to be ultra-low along 'c' direction for the bulk (0.44 Wm/K) and the same along 'b' direction for monolayer (0.36 Wm/K). We also predict a great potential for nanostructuring with 72% reduction in the thermal conductivity for the crystal grain size of 10 nm. Further, carrier lifetimes for various concentrations and temperatures are estimated by incorporating different scattering mechanisms in the calculations, such as acoustic deformation scattering (ADP), ionized impurity scattering (IMP) and polar optical scattering (POP). Based on thermoelectric performance, we predict n-type doping would be more favourable. At 700 K, n-type bulk has a maximum thermoelectric performance (ZT) of 0.4, higher than the well-known monoclinic GaTe (0.24) TE material. In addition, the calculated absorption coefficient reveals the optical anisotropy. The predicted absorption coefficients for bulk and monolayer in the visible range are 7 . 5 × 1 0 5 / cm and 3 × 1 0 5 / cm, respectively. The current work highlights its extremely low thermal conductivity and significant absorption coefficients, which could lead to future applications in thermoelectric and optical devices. Graphical abstract: Highlights: The thermoelectric properties of bulk and monolayer NbS 2 Cl 2 are investigated. Calculated lattice thermal conductivity( κ l ) of bulk and monolayer are found to be ultra-low. Nano-structuring could lead to reduction of κ l upto 72 % with grain size of 10 nm. ADP, IMP and POP mechanisms are considered in calculating the carrier scattering rates. The studied compound favours n-type carrier in both bulk and monolayer.